REGULASI NON-FUNGIBLE TOKEN SEBAGAI UPAYA KEAMANAN TERHADAP PEMBAJAKAN HAK KEKAYAAN INTELEKTUAL - Daenila, Nurmala; Hasanah, Nurul (Faculty of Law, Universitas Tanjungpura, 2025)
AbstractNon-Fungible Token (NFT) represents a symbol of the future in a market that increasingly adapts to modern times. NFT provides a profitable platform for digital art aiming to monetize their works more effectively and efficiently. However, NFTs are sometimes misused by others to profit from an artist